Factors associated with long-term pessary use in women with symptomatic pelvic organ prolapse. (3rd September 2019) - Mao, M.; Xu, T.; Kang, J.; Zhang, Y.; Ai, F.; Zhou, Y.; Zhu, L.
Abstract: Objectives: This study aimed to evaluate the continuation rate and identify the factors associated with long-term pessary use, which are essential for counseling women with symptomatic pelvic organ prolapse (POP) seeking long-term pessary treatment. Methods: This prospective observational study included 277 patients who had successful pessary fittings between April 2015 and November 2016. All patients were followed until April 2018. Data analysis was performed with independent-samples t -tests, non-parametric tests, chi-square tests, and logistic regression. Results: The median (range) follow-up time was 26 (17–36) months; 76.5% of patients continued to use pessaries at the study endpoint. Sixty-one patients discontinued pessary use, and almost all of them (55/61, 90.2%) discontinued pessary use within the first 12 months after successful pessary fitting. A total vaginal length (TVL) < 7.5 cm (odds ratio [OR], 0.181; 95% confidence interval [CI], 0.062–0.524; p =  0.002) and a lower baseline Pelvic Organ Prolapse Distress Inventory 6 (POPDI-6) score (OR, 0.974; 95% CI, 0.954–0.994; p =  0.013) were independent factors associated with pessary discontinuation. Conclusion: TVL ≥ 7.5 cm and a higher baseline POPDI-6 score were independent factors associated with long-term pessary use after successful fitting in women with symptomatic POP.